HIPEROKSALURIA PRIMER - Harun, Haerani (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2019)
ABSTRACTPrimary hyperoxaluria is an autosomal recessive disorder that involves excessive production of oxalate. Primary hyperoxaluria consists of three types based on the definition of hereditary enzymes namely PH1, PH2, PH3. Hyperoxaluria and CaOx crystals are the main symptoms of all types of PH with urinary oxalate levels> 0.8 mmol / 1.73 m2 per day. Systemic oksalosis occurs at the critical point of plasma supersaturation ie> 30 µmol / L, usually occurring at the onset of renal insufficiency. Oxalate deposits can occur in various organs except the liver and can cause morbidity. A definitive diagnosis for patients with clinical symptoms PH requires genetic testing. PH treatment includes high fluid consumption, diet modification, pharmacological treatment, kidney stone removal and organ transplantation.Keyword: Primary hyperoxaluria, Oxalate, Systemic oksalosis ABSTRAKHiperoksaluria primer adalah suatu kelainan resesif autosomal yang melibatkan produksi berlebihan oksalat. Hiperoksaluria primer terdiri atas tiga jenis berdasarkan defieinsi enzim herediter yaitu PH1, PH2, PH3.Hiperoksaluria dan kristal CaOx adalah gejala utama semua tipe PH dengan kadar oksalat urin >0.8 mmol/1.73 m2 perhari. Oksalosis sistemik terjadi pada titik kritis supersaturasi plasma yaitu >30 µmol/L, biasanya terjadi pada awal insufisiensi ginjal. Deposit oksalat dapat terjadi pada berbagai organ kecuali hati dan dapat menyebabkan morbiditas. Diagnosis defenitif untuk pasien dengan gejala klinis PH memerlukan pemeriksaan genetik. Pengobatan PH antara lain dengan konsumsi cairan yang tinggi, modifikasi diet, pengobatan farmakologi, pengangkatan batu ginjal dan transplantasi organ.Kata Kunci: Hiperoksaluria Primer, Oksalat,Oksalosis Sistemik